2019
DOI: 10.3892/etm.2019.7967
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing involvement of NK cells in psoriasiform dermatitis animal model

Abstract: Psoriasis (Ps) is a chronic inflammatory immunemediated disease with skin and joint manifestations, characterized by abnormal and rapid proliferation of keratinocytes and infiltration of psoriatic lesions with immune cells. Extensive literature suggests that Ps is a T-cell mediated disease its pathogenesis being highly related to innate and adaptative immune cells. Although natural killer (NK) cells are involved in the inflammatory process of Ps through pro-inflammatory cytokine secretion (tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In the imiquimod-induced psoriasis-like dermatitis mouse model, NK cells are decreased in the peripheral blood and spleen [108]. However, the role of NK cells in psoriasis mouse models remains unclear, although NK cell maturation markers, such as CD11b, CD43, CD27, and killer cell lectin-like receptor G1 (KLRG1), increase in peripheral blood and spleen NK cells from imiquimod-treated mice [109]. Furthermore, alterations in maturation marker expression are correlated with disease severity [109].…”
Section: Nk Cells In Mouse Models Of Psoriasismentioning
confidence: 99%
“…In the imiquimod-induced psoriasis-like dermatitis mouse model, NK cells are decreased in the peripheral blood and spleen [108]. However, the role of NK cells in psoriasis mouse models remains unclear, although NK cell maturation markers, such as CD11b, CD43, CD27, and killer cell lectin-like receptor G1 (KLRG1), increase in peripheral blood and spleen NK cells from imiquimod-treated mice [109]. Furthermore, alterations in maturation marker expression are correlated with disease severity [109].…”
Section: Nk Cells In Mouse Models Of Psoriasismentioning
confidence: 99%
“…For NK cells phenotypic characterization we used a large panel of surface markers including activation, maturation, and markers for cytokine receptors. The results showed important differences in IMQtreated mouse NK cell phenotype as compared to controls [83]. Taking into account the recently found relation between gut microbiota and Ps initiation, we have demonstrated that oral ingestion of IgY raised against pathological gut bacteria resistant to antibiotics can alleviate psoriatic lesions and restore immune parameters [18].…”
Section: Immune Cells Like Activated Dermal Dcs Can Circulate Through...mentioning
confidence: 84%
“…IgY was isolated from the yolk of hyperimmune eggs laid by chickens immunized with human pathogenic bacteria that are antibiotic-resistant, namely groups of pathogens with a high rate of antibiotic resistance responsible for the majority of nosocomial infections. IgY was obtained according to the methodology described in the patent [ 45 ]. The obtained IgY is an original product of the ROMVAC Company and is part of the IMUNOINSTANT brand having a European trademark (EUIPO).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were monitored daily. The experiments were conducted in accordance with recognized principles of laboratory animal care in the framework of EU Directive 2010/63/EU [ 45 ] and the study was comprised in a research project that was approved by the Ethics Committee from Victor Babeș Institute (Approval no 88/20 January 2021) and National Sanitary Veterinary and Food Safety Authority (Approval no 598/8 February 2021).…”
Section: Methodsmentioning
confidence: 99%